2017
DOI: 10.1128/jvi.00288-17
|View full text |Cite
|
Sign up to set email alerts
|

A Lipopeptide HIV-1/2 Fusion Inhibitor with Highly PotentIn Vitro,Ex Vivo, andIn VivoAntiviral Activity

Abstract: Peptides derived from the C-terminal heptad repeat (CHR) region of the human immunodeficiency virus type 1 (HIV-1) fusogenic protein gp41 are potent viral entry inhibitors, and currently, enfuvirtide (T-20) is the only one approved for clinical use; however, emerging drug resistance largely limits its efficacy. In this study, we generated a novel lipopeptide inhibitor, named LP-19, by integrating multiple design strategies, including an N-terminal M-T hook structure, an HIV-2 sequence, intrahelical salt bridge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 51 publications
0
72
0
Order By: Relevance
“… Importantly, anchoring C34 peptide on cell surface also enhance the peptide's stability, as the antiviral activity appeared to be persistent following extensive wash . Similar lipid peptide‐based HIV fusion inhibitors were reported . The dramatically enhanced inhibitory potency and stability, combined with the >300‐fold increase in plasma concentration, make this amphiphilic strategy attractive in blocking many other virus entry during infections.…”
Section: Clinical and Preclinical Examples Of Amphiphilic Drugsmentioning
confidence: 68%
“… Importantly, anchoring C34 peptide on cell surface also enhance the peptide's stability, as the antiviral activity appeared to be persistent following extensive wash . Similar lipid peptide‐based HIV fusion inhibitors were reported . The dramatically enhanced inhibitory potency and stability, combined with the >300‐fold increase in plasma concentration, make this amphiphilic strategy attractive in blocking many other virus entry during infections.…”
Section: Clinical and Preclinical Examples Of Amphiphilic Drugsmentioning
confidence: 68%
“…However, the potent stability of SARS-CoV-2 6-HB structure might reduce the antiviral efficacy of EK1. Recently, numerous reports have shown that the lipidation strategy can effectively improve the antiviral activity of fusion inhibitory peptides, such as the ant-HIV-1 peptide LP-19, 18 and the anti-Nipah virus lipopeptides. 19 In order to improve the inhibitory activity of EK1, cholesterol (Chol) and palmitic acid (Palm) were covalently attached to the Cterminus of EK1 sequence under the help of a flexible polyethylene glycol (PEG) spacer, and the corresponding lipopeptides EK1C and EK1P were constructed, respectively ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Among all the viruses causing human diseases, none has ever caused more concern worldwide than HIV, with more than 36 million people infected [139]. The currently available antiviral treatment targets four steps of the viral cycle: viral entry, reverse transcription, integration, and virion maturation [140]. However, since HIV-1 and HIV-2 have different evolutionary histories, sharing only 50% of genetic similarity, most antivirals are capable of inhibiting only HIV-1, and a few inhibit HIV-2 [141,142].…”
Section: Human Immunodeficiency Virusmentioning
confidence: 99%
“…The results showed that LP-19 could inhibit HIV-1, -2 and SIV in much lower concentrations than 2P23, especially in the assay for inhibition of virus entry. The lipid conjugation strategy improved the peptide's binding stability and antiviral activity in both in vitro and ex vivo assays, providing a good candidate for drug development [140].…”
Section: Human Immunodeficiency Virusmentioning
confidence: 99%